Attention/Working Memory and Executive Function in Parkinson's Disease: Review, Critique, and Recommendations - Biundo, Roberta; Bezdicek, Ondrej; Cammisuli, Davide Maria; Cholerton, Brenna; Dalrymple‐Alford, John C.; Edelstyn, Nicola; Fiorenzato, Eleonora; Holker, Erin; Martinez‐Horta, Saul; Martini, Alice; Santangelo, Gabriella; Segura, Barbara; et al. (Movement disorders, 2025)
Background Cognitive impairment in Parkinson's disease (PD) is a well‐established non‐motor complication that significantly affects the quality of life and well‐being of both patients and care partners. To optimally detect mild cognitive impairment or dementia, extensive neuropsychological assessment is essential. A wide range of cognitive tests and clinical outcome assessments have been used in clinical settings, often without regard to their clinimetric quality. Methods We performed a literature review of tests assessing attention/working memory and executive domains in PD (tests on other domains are included in an accompanying review). The selected tests were evaluated for their clinimetric properties and categorized by a panel of experts as “recommended,” “recommended with caveats,” “suggested,” or “listed” according to the International Parkinson and Movement Disorder Society Clinical Outcome Assessment Scientific Evaluation Committee guidelines. Results A total of 30 tests were reviewed. Eight tests were “recommended,” including four tests assessing attention/working memory abilities (WAIS‐IV Digit Span, Coding and Symbol Search subtests, and Trail Making Test) and four tests assessing executive abilities (WAIS‐IV Similarities, Wisconsin Card Sorting Test, Fluency Tests, and Stroop Color‐Word Test). These tests demonstrated good to excellent levels of reliability and validity, have normative datasets, and are sensitive to change. Eight other tests were “recommended with caveats”, eleven were “suggested,” and three were “listed.” Conclusions The recommended tests for attention/working memory and executive functioning in PD can guide PD cognitive assessment. Other tests were identified as potentially useful; however, caution is advised due to their clinimetric limitations. Further validation studies are required for these tests. © 2025 The Author(s). Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.